Calibration in EFL Reading: Examining The Nature of Judgment of Confidence - Neupane, Madhu (Tribhuvan University Journal, 2016)
This article examines the nature of English as a foreign language (EFL) learners’ appraisal confidence and appraisal calibration in EFL reading comprehension. Appraisal confidence refers to the degree to which test takers identify the probability that their test answer is corrector appropriate in percentage terms (e.g., 0%, 25%, 50%, 75%, or 100%).Appraisal calibration refers to the accuracy of test takers’ appraisal confidence by comparing their appraisal confidence to their test performance in percentage terms. Two hundred and three students studying Master of Education (M. Ed) with specialization in English in the Tribhuvan University participated in the study. An EFL reading comprehension test specially designed for the study and appraisal confidence rating scales incorporated in the same reading comprehension test were used as the tools for data collection. The findings of the study show that the students were highly overconfident in their reading comprehension because the difference between their average appraisal confidence (86.84) and average accuracy in performance (52.35) was+34.49. The implications of the study and recommendations for further research are discussed.